Current topics in catecholaminergic polymorphic ventricular tachycardia. Issue 5 (24th November 2015) - Sumitomo, Naokata
Abstract: Catecholaminergic polymorphic ventricular tachycardia (CPVT) is induced by emotions or exercise in patients without organic heart disease and may be polymorphic or bidirectional in nature. The prognosis of CPVT is not good, and therefore prevention of sudden death is of utmost importance. Genetic variants of CPVT include RyR2, CASQ2, CALM2, TRD, and possibly KCNJ2 and ANK2 gene mutations. Hypotheses that suggest the causes of CPVT include weakened binding of FKBP12.6 and RyR2, a store overload‐induced Ca 2+ release (SOICR), unzipping of intramolecular domain interactions in RyR2, and molecular and functional abnormalities caused by mutations in the CASQ2 gene. The incidence of an RyR2 anomaly in CPVTs is about 35–79%, whereas anomalies in the CASQ2 gene account for 3–5% CPVTs. The ping‐pong theory, suggesting that reciprocating delayed after depolarization induces bigeminy of the right and left bundle branches, may explain the pathogenesis of bidirectional ventricular tachycardia. Flecainide, carvedilol, left sympathetic nerve denervation, and catheter ablation of the PVC may serve as new therapeutic strategies for CPVT while gene‐therapy may be applied to some types of CPVT in the future. Although, not all sudden cardiac deaths in CPVT patients are currently preventable, new medical and interventional therapies may improve CPVT prognosis.